Flash Card to Improve Expressive Language in Children with Mild Intellectual Disabilities - Rizki Ramadhana; Budi Susetyo; Imas Diana Aprilia (INCLUSIVE EDUCATION, 2023)
The problems of intellectual disability children who experience expressive language difficulties need to get the right solution so that these difficulties can be overcome and get learning services that suit their abilities and needs. Based on these problems the researcher developed Flash Card media which has a very important role to make it easier for children to perceive something. learning to read technical reading is one of them because it is difficult to think abstractly, so the teacher can work around this by using media that is in accordance with the goals and material being taught. The way to overcome these problems is to develop learning media that are suitable for children's abilities. Media is needed to make it easier for intellectual disability children to learn. The method used is a descriptive qualitative approach.